Os elos da cadeia produtiva industrial brasileira: uma análise via matriz insumo-produto para 1990, 2000 e 2010 - Silva, Guilherme Jorge da (2019)
Brazilian industrialization, carried out 50 years (1930-1980) by the process of import substitution, takes place in the post-war context where Latin American countries try to reduce their productive differences with the developed countries. CEPAL, the UN agency responsible for promoting and analyzing the region's development, has in Raul Prebisch the seminal work that explains the conditions of these countries, in a scenario of deterioration of terms of trade in the international market and in a dynamic between center and periphery, where developed countries absorb the benefits of technological progress from the periphery. To break this cycle, the path to the development and incorporation of technology must be industrialized. Among the influences of the school, not only Keynesian thought but also Joseph Schumpeter's, especially in the importance of technological incorporation and in the economic cycles of the countries. The 1990’s renew CEPAL structuralist thinking, incorporating concepts from the neoschumpeterian current to understand the difficulties of internalization of technical progress. This current explores the fact that, despite Brazil's industrialization, especially in the metalworking sector of the fourth technological revolution, it failed to fit perfectly into the 1970’s in the industrialization of the fifth technological, telecommunications, and information technology revolution. This work aims to verify the relations of the Brazilian industrial fabric, analyzing through input-output made available by IBGE for the years 1990, 2000 and 2010, the following indicators: Forward Linkage (FL), Backward Linkage (BL), Power of Dispersion (PD), Dispersion Sensitivity (SD) and Coefficient of Variation (CV). The results found for the period analyzed indicate a specialization for the traditional and commodity sectors, with strong productive links for durables only in the year 2010 and poor results for the diffusion sectors of technology throughout the analyzed period.